Consumers’ Purchase Intention: Influencing Factors Unveiled at Korean Thematic Café (Case Study: Chingu Café) - Wandebori, Harimukti; Wijaya, Vinon (TRIKONOMIKA, 2017)
Service quality, atmosphere, and food quality have become an important part to be considered by a firm or company in order to attract consumers and to compete in the marketplace. This research will be taking Chingu Café which is located in Bandung, Indonesia to be the object of the study. This research applied a quantitative method with total sample of 384 respondents who have visited and spent time in Chingu Café. A multi linear regression was applied to analyze the findings in order to gain the effect of service quality’s dimensions, food quality, and atmosphere on purchase intention. This research is able to gather unique findings in a Korean thematic café business. It is obtained that the most consumptive consumers are teenagers and young-adults dominated by females. More importantly, this research is able to find that service quality (tangible, reliability, responsiveness, and empathy), atmosphere, and food quality have a positive influence on purchase intention while none of such relationship between assurance dimension and purchase intention.